Pengaruh Smma (Social Media Marketing Activities) Tiktok Terhadap Kesediaan Untuk Membayar Harga Premium Produk Makeover Yang Dimediasi Oleh Citra Merek dan Loyalitas Merek - Isthiqomah, Monica Riskiana Nur; Soepatini, Soepatini (YUME : Journal of Management, 2024)
This research aims to investigate how TikTok's Social Media Marketing Activities (SMMA) influence consumers' readiness to pay higher prices for MakeOver products, with Brand Image and Brand Loyalty as mediating factors. The study employs a quantitative approach, utilizing non-probability purposive sampling to select 185 Indonesian consumers who have purchased MakeOver products. Data was collected via questionnaires using a Likert scale. The analysis employs PLS SEM, involving Outer Model Analysis and Inner Model Analysis conducted with SMARTPLS 3.0 software. The findings indicate a significant and positive relationship between SMMA and the willingness of consumers to pay premium prices, mediated through Brand Image and Brand Loyalty.